Body-oriented interventions to promote preschoolers’ social–emotional competence: a quasi-experimental study - Dias Rodrigues, Andreia; Marmeleira, José; Pomar, Clarinda; Lamy, Elsa; Guerreiro, Daniela; Veiga, Guida (Frontiers in Psychology, 2023)
Introduction Social–emotional competence is foundational to children’s health and well-being. Body-oriented interventions, such as relaxation or play based interventions, have been shown to promote social–emotional competence, however more studies are needed to better understand the specific benefits of each type of body-oriented approach. Objective The present study aimed to examine the chronic and the acute effects of three body-oriented intervention programs (loose parts play, relaxation and combining loose parts play and relaxation) on preschoolers’ social–emotional competence. Methods A quasi-experimental study was carried out, including 62 preschoolers (4.44 ± 0.93 years) that were allocated into 4 groups: Loose Parts Play program (n = 17); Relaxation program (n = 17); Combined program (n = 13); and Waitlist Control Group (no intervention; n = 15). All three intervention programs had a 12-week duration, with biweekly sessions of 30-min, implemented in the preschool outdoors. To examine the chronic effects of the intervention programs, all instruments (parents’ and preschool teacher’s questionnaires, tasks and saliva) were collected at baseline and after the 12-week period. To examine the acute effects, saliva samples were collected immediately before and after the 1st and the 24th sessions, with a total of 4 collections per child. Results Both loose parts play and relaxation interventions significantly improved (p < 0.05) children’s positive emotion expression. Several within-groups changes were found for the Loose parts play, Relaxation and Combined programs. Conclusion Body-oriented interventions effectively promote preschoolers’ social–emotional competence.